Identifying Directions for Russia’s Science and Technology Cooperation - Maxim Kotsemir; Tatiana Kuznetsova; Elena Nasybulina; Anna Pikalova (Foresight and STI Governance)
Strong international partnerships are a key vehicle for building an efficient national innovation system. Successful global cooperation needs comprehensive knowledge of the features of the science and technology (S&T) sphere in a changing environment of global division of labour, competition, and political climates. New realities and trends emerge, changing the established ‘rules of the game’ and calling for immediate actions from politicians, experts, and various economic actors. We propose an analytical approach to build and examine an empirical database. Drawing on bibliometric analysis and expert survey tools, such an approach helps us identify the most promising areas for Russia’s international S&T cooperation. We assess the scope for applying the proposed methodology. Based on the latest available data in Web of Science, the international scientific citation indexing service (2014 and early 2015), we compare the structure and variation over time of scientific specializations in Russia, leading S&T countries, and several fast growing global economies. The cooperation priorities that we identified via matrix analysis were complemented with data from expert surveys. The surveys highlighted the partner organizations, thematic areas, and instruments of S&T cooperation, which indicate some of the future possibilities for Russia’s international S&T cooperation.